2005
DOI: 10.1603/0022-0493-98.2.367
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Honey Bee (Hymenoptera: Apidae) Density on the Production of Canola (Crucifera: Brassicacae)

Abstract: Pollination is an essential step in the seed production of canola, Brassica napus L. It is achieved with the assistance of various pollen vectors, but particularly by the honey bee, Apis mellifera L. Although the importance of pollination has been shown for the production of seed crops, the need to introduce bee hives in canola fields during flowering to increase oil seed yield has not yet been proven. With the purpose of showing this, hives of A. mellifera were grouped and placed in various canola fields in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
34
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 4 publications
5
34
0
1
Order By: Relevance
“…Besides contributing to the preservation of natural ecosystems, bee pollination is one of the main sources for improvement of crop productivity (Mahmoud, 2012). Thus honey bees, A. mellifera, are considered the most important flower visitors (Delaplane & Mayer, 2000) and most efficient B. napus pollinators (Free, 1993;Sabbahi et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Besides contributing to the preservation of natural ecosystems, bee pollination is one of the main sources for improvement of crop productivity (Mahmoud, 2012). Thus honey bees, A. mellifera, are considered the most important flower visitors (Delaplane & Mayer, 2000) and most efficient B. napus pollinators (Free, 1993;Sabbahi et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The latter secrete a greater amount of nectar, with high concentrations of sugars, and are more easily accessible to insects during the entire anthesis period (Williams, 1980). Even though B. napus is considered a self-compatible crop (Williams, 1978;Eisikowitch, 1981), susceptible to wind pollination (Gene Technology Regulator, 2002), the foraging bees increase its productivity rate (McGregor, 1976;Delaplane and Mayer, 2000;Sabbahi et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Sabir et al (2000) found that honeybees maximized seed yield, 1000-grain seed yield and germination percentage in Brassica campestris. Sabbahi et al (2005) found a significant improvement in the seed yield when honeybees were present. Munawar et al (2009) reported significant increases in a range of plant parameters when caged with bees as compared to plants without bees.…”
Section: Discussionmentioning
confidence: 91%